The Effect of Sustainability Report on the Financial Performance of Consumer Goods Companies - Nurusyifa Amelia; Aginsha Caurel N; Melinda Magdarina; Maria Yovita R. Pandin (Business and Investment Review, 2023)
This research aims at how the influence that will arise from the disclosure of economic performance, environmental performance and social performance on the companies financial performance. This research uses a type of quantitative research. The population used in this research is Consumer Goods companies that have been listed on the Indonesia Stock Exchange in the period 2021 – 2022. Samples that can be generated in this research a number of 10 data. The method used in this research is purposive sampling method and using SPSS 22 Analysis tool. The results of this research indicate that the disclosure of economic performance is not a positive and insignificant influence on financial performance, disclosure of environmental performance is not a positive influence on financial performance and disclosure of social performance is a negative influence on financial performance. The implication of this research is that it can be useful to be able to determine the effect of what will happen between the sustainable report and how the company generates profits that are interrelated with the financial performance of Consumer Goods companies.